Standard terminology is critical to advancing rehabilitation and assistive technology: a call to action. (17th November 2022) - Elsaesser, Linda-Jeanne; Layton, Natasha; Scherer, Marcia; Bauer, Stephen
Abstract: This perspective piece discusses inconsistencies in assistive technology (AT) language as a barrier to communication in AT provision, research, development, trade, and policy. The imperative to improve communication is explored in relation to AT stakeholder endeavours. This commentary is a call for action to develop a terminology standard through the aggregation of evidence-based concepts and terms to inform and optimize stakeholder outcomes. IMPLICATIONS FOR REHABILITATION: Standardized terminology supports the gathering, aggregation, analysis, and interpretation of valid data and the development of tools used for needs and outcomes assessment. Standardized terminology also supports effective and efficient documentation, practice, collaboration, and capacity building by stakeholders in both national and international contexts.